Palaeo‐environment in an ancient low‐latitude, arid lacustrine basin with loessite: The Smith Bank Formation (Early Triassic) in the Central North Sea, UK Continental Shelf. Issue 2 (10th July 2017) - Wilkins, Anne D.; Hurst, Andrew; Wilson, Michael J.; Archer, Stuart
Abstract: Predominantly fine‐grained strata were deposited in the Smith Bank Formation (Early Triassic) in the Central North Sea area of the Northern Permian Basin. Previously regarded as monotonous red claystone, examination of continuous core reveals abundant stratification, significant variation in colour, siltstone as the prevalent average grain size, and claystone is rare. Loessite occurs beyond the north‐western lacustrine margin, and aerosol dust has inundated clay pellets derived from aeolian reworking of the desiccated lake floor. The loessite has limited evidence of pluvial reworking but rare fossil roots testify to sufficient moisture to sustain plants. Loessite has not previously been differentiated successfully from other fine‐grained strata in the subsurface, but this study defines the presence of random grain‐fabric orientation as an intrinsic unequivocal characteristic of loessite that formed during air‐fall deposition of aerosol dust. Comparison with outcrop data verifies the utility of grain fabric to differentiate loessite. Tosudite, an aluminous di‐octahedral regularly ordered mixed‐layer chlorite/smectite, which is rare in sedimentary rock, forms a significant proportion (10 to 21%) of the clay mineral fraction of loessite along with a similar quantity of kaolinite. In all other samples, only illite and chlorite are identified, which is typical of fine‐grained Triassic strata. In a location, close to the southern lake margin, lacustrine strata are characterized by fining‐upward couplets of very fine‐grained sandstone into siltstone and mudstone, with occasional desiccated surfaces. Small sand injections and associated sand extrusions are common and indicate periodic fluidization of sand. Precise stratigraphic location of the Smith Bank Formation is problematic because of extremely sparse fossil preservation; however, there is no sedimentological evidence for a period of hyperaridity known from the early Olenekian in continental Europe, which may mean that the North Permian Basin was never hyperarid or that the Smith Bank Formation is restricted to the Induan.